The Influence of Thickness on the Mechanical Behaviors of 3D Printing Resins for Orthodontic Retainers - Theerasak Nakornnoi; Patamaporn Bunjerdjin; Peerapong Santiwong; Kawin Sipiyaruk; Siew Peng Neoh; Rochaya Chintavalakorn (International Journal of Biomaterials)
This study aimed to evaluate the mechanical behaviors of thermoformed and 3D-printed retainers with different thicknesses. Thermoformed retainers (Duran) and 3D-printed retainers (Dental LT Clear V2 and NextDent Ortho Flex) were fabricated at thicknesses of 0.5, 0.75, and 1 mm. Five samples of each material were subjected to compression, tensile, and flexural testing with the universal testing machine (Instron Ltd., Buckinghamshire, England). The results revealed that the mechanical behaviors were significantly influenced by thickness in each type of material. The increased thickness tended to increase strength and modulus in all three tests. However, Dental LT Clear V2 and Duran showed that flexural strength and modulus were inversely related to thickness. The compressive test revealed significantly greater compressive resistance in 3D-printed groups, except for the NextDent Ortho Flex at 0.5 mm. The tensile test showed that Dental LT Clear V2 at all thicknesses demonstrated significantly higher tensile strength and modulus, while NextDent Ortho Flex was significantly lowest at any thickness in tensile and flexural properties. In conclusion, the thickness significantly influenced the mechanical behaviors of the 3D-printed retainers. The 0.75 mm thickness of Dental LT Clear V2 could be considered as an alternative to fabricated retainers due to its similar mechanical properties compared with the thermoformed material.